2002
DOI: 10.1590/s0101-81752002000500004
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição vertical e flutuação sazonal da macrofauna vágil associada a Sargassum cymosum C. Agardh, na praia do Lázaro, Ubatuba, São Paulo, Brasil

Abstract: ABSTRACT. Depth distribution and seasonal fluctuations of vagile macrofauna associated with Sargassum cymosum C. Agardh at Lázaro beach, Ubatuba, São Paulo, Brazil. Seasonal tluctuations and depth distribution of the vagile macrofauna associated with Sargassum cymosum at Lazaro beach, Ubatuba, São Paulo State, were evaluated through density comparison of higher taxonomic groups among three depth intervals in four periods of the year. Ten groups were identified and among them gammarid and caprellid amphipods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
1
19
0
13
Order By: Relevance
“…Gammarid amphipods are important meso-herbivores on macroalgal communities, grazing on Sargassum and associated epiphytes (JACOBUCCI & LEITE 2008). JACOBUCCI & LEITE (2002) observed that the abundance of gammarid amphipods associated with S. cymosum from Lázaro beach was higher during winter (minimum hydroid cover) and lower during summer, which coincides with the period of maximum hydroid algal cover recorded in this study. Their grazing activity on S. cymosum during the period of their maximum abundance (winter) may have contributed to the lower levels of hydroid algal cover recorded in this season.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Gammarid amphipods are important meso-herbivores on macroalgal communities, grazing on Sargassum and associated epiphytes (JACOBUCCI & LEITE 2008). JACOBUCCI & LEITE (2002) observed that the abundance of gammarid amphipods associated with S. cymosum from Lázaro beach was higher during winter (minimum hydroid cover) and lower during summer, which coincides with the period of maximum hydroid algal cover recorded in this study. Their grazing activity on S. cymosum during the period of their maximum abundance (winter) may have contributed to the lower levels of hydroid algal cover recorded in this season.…”
Section: Discussionsupporting
confidence: 84%
“…This area presents large and continuous macroalgal beds that extend from the infralittoral fringe to approximately 4 m deep, and is moderately sheltered from wave action (JACOBUCCI & LEITE 2002). Sargassum cymosum is dominant in the area but other species of algae such as Dictyopteris delicatula Lamouroux may be found in lower abundances (SZÉCHY & PAULA 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Marine macrophyte faunas are often dominated by gammarideans, crustaceans that may select areas with more availability of food and refuges against predators and unfavorable conditions (BUSCHMANN 1990). On the other hand, similar, relatively low numbers of turbellarians, pycnogonids and ophiuroids in the treatments and natural conditions, were also detected in other Sargassum studies in this region (JACOBUCCI & LEITE 2002), and these groups occurred in low abundance on the Sargassum fronds before the treatment.…”
mentioning
confidence: 51%
“…The phytal community associated with marine macrophytes is highly diverse in composition, and in the characteristics of the species that constitute it (JACOBUCCI & LEITE 2002). The phytal supports large faunal densities and species richness (SCHNEIDER & MANN 1991), because of the large number of microhabitats offered (WALTHERS & WETHEY 1996) and the interactions among macrophytes, epiphytic algae and invertebrates, functioning on many different spatial and temporal scales (JERKANOFF et al 1996, DUFFY & HAY 2000.…”
mentioning
confidence: 99%
“…The organisms that form these substrates are considered ecosystem engineers, increasing local habitat complexity and therefore infl uencing biodiversity patterns (Voultsiadou et al, 2007). Biogenic substrates such as sponges (Duarte & Nalesso, 1996;Ribeiro et al, 2003;Marin, 2007;Garcia et al, 2009), sabellariid polychaetes (Nalesso et al, 1995;Bosa & Masunari, 2002a,b), bryozoans (Conradi et al, 2000;Morgado & Tanaka, 2001), mussels (Jacobi, 1987;O'Connor & Crowe, 2007), barnacles (Crain & Bertness, 2006), ascidians (Castilla et al, 2004) and macroalgae (Tararam & Wakabara, 1981;Masunari, 1982;Jacobucci & Leite, 2002;Tanaka & Leite, 2003) shelter a rich and diverse fauna in varied types of association, including commensalism, mutualism and parasitism.…”
mentioning
confidence: 99%